(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2004)
Surabaya, to be considered from the national scope, they have an important role/function for the development of its district; whereas from regional scope, they have acted as development central for its province. Since the city,s condition was not ready toaccept this situation, then this makes aresult to many dirty/improper places every where, as it has been caused by the low income work-seeker,need for house. So, as one alternative for making the city propely, we have done many improvement from every aspect, i.e. : by developing those illegal/improper location and further to place the occupants from those illegal/improper places/location to the stories houses. The results of this observation have shown the following ; this gathering room is necessary tobe built up ; this gathering room should be placed relatively close to the house location ; this gathering room, from religious side, could be approved ; this gathering room is necessary to be built up for fulfilling the human life purpose (e.g.: washing, bathroom/toilet), whereas the facility for cloth - drying ; this gathering cooking room, is still necessery for occupant but the condition will be made more privately. Abstract in Bahasa Indonesia : Secara nasional, Surabaya berperan dalam pembangunan wilayah; sedangkan lingkup regional sebagai pusat pengembangan wilayah propinsi, konsekwensinya timbul arus urbanisasi besar-besaran dari desa ke kota. Disebabkan kondisi kota tidak siap menerima, timbul kekumuhan karena pencari kerja membutuhkan tempat tinggal. Peremajaan merupakan alternatif menertibkan kota, dan menempatkan warga kedalam Rumah Susun. Disimpulkan bahwa ; adanya ruang bersama, tetap diperlukan ; keberadaan ruang bersama, sebaiknya yang penempatannya relatif dekat hunian warga ; keberadaan ruang bersama, untuk kegiatan "keagamaan", dapat diterima sebagaimana adanya ; keberadaan ruang bersama, untuk menunjang kehidupan warga (cuci,kamar mandi/WC) masih diperlukan ; keberadaan dapur bersama, masih diperlukan warga, dan sebaiknya lebih bersifat pribadi. Kata kunci: rumah susun, penghuni berpenghasilan rendah, ruang bersama.